1994
DOI: 10.1111/j.2042-3306.1994.tb04051.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Equid herpesvirus‐1 (EHV‐1) in the respiratory tract of ponies: implications for vaccination strategies

Abstract: Summary Twelve adult ponies and 2 conventional foals were exposed to 106.6 TCID50 of Equid herpesvirus‐1 (EHV‐1), strain Ab4 and samples of respiratory tract tissues were recovered. Infectious virus in tissue homogenates was detected using susceptible cell monolayers and expression of viral antigens was monitored using indirect immunoperoxidase histochemistry of paraffin sections. The results illustrated the rapid dissemination of EHV‐1 throughout the respiratory tract, with early replication in the lungs one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 18 publications
4
34
0
4
Order By: Relevance
“…viremia followed by infection of the endothelium of the pregnant uterus and the central nervous system (secondary replication) (Allen and Bryans, 1986;Edington et al, 1986;Kydd et al, 1994). Although the exact identity of EHV1-infected cells during primary replication and viremia remains a matter of debate, a recent in vivo study demonstrated that most infected cells in the respiratory submucosa, draining lymph nodes and the blood are positive for the cell surface marker CD172a (Gryspeerdt et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…viremia followed by infection of the endothelium of the pregnant uterus and the central nervous system (secondary replication) (Allen and Bryans, 1986;Edington et al, 1986;Kydd et al, 1994). Although the exact identity of EHV1-infected cells during primary replication and viremia remains a matter of debate, a recent in vivo study demonstrated that most infected cells in the respiratory submucosa, draining lymph nodes and the blood are positive for the cell surface marker CD172a (Gryspeerdt et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Theoretically, control of infection is therefore possible either by preventing infection at the mucosal surface or alternatively by hindering dissemination of virus once infection is established. Previous experiments have demonstrated rapid adsorption, penetration and replication of EHV-1 in equine respiratory epithelium, nasopharyngeal and pulmonary interstitium and endothelium within 12 h of infection (Kydd et al 1994). This implies that in the absence of mucosal immunity, EHV-1 infection is disseminated rapidly and therefore the clearance of intracellular virus by the host relies on humoral and cellular immune responses.…”
Section: Introductionmentioning
confidence: 97%
“…It is also the primary replication site of EHV-1, as it is for most alphaherpesviruses (Kydd et al, 1994a;Van Maanen, 2002;Van Maanen & Cullinane, 2002;Gryspeerdt et al, 2010). Subsequently, the virus disseminates via a leukocyte-associated viraemia, which enables EHV-1 to reach end-vessel endothelia in the uterus and central nervous system (Allen & Bryans, 1986;Kydd et al, 1994b). In these organ systems, virus replication can result in vasculitis and perivasculitis, ultimately resulting in abortion and myeloencephalopathy, respectively.…”
Section: Introductionmentioning
confidence: 99%